Internet addiction of daughters of alcoholics and their relationships with alcoholic parents - Pawłowska, Beata; Potembska, Emilia; Gleba, Elżbieta; Kalinowska-Tomala, Joanna; Krawczyński, Konrad (Current Problems of Psychiatry, 2011)
The aim of this study was to find answers to the following research problems (issues) :• Are there any differences in the symptoms of internet addiction among girls who are children of alcoholics and those who do not have alcoholic parents and what are they ?• Are there any dependencies between the symptoms of internet addiction and family relationships in the families of daughters of alcoholic parents and what are they ?Methods and the examined group: The investigation included a group of 216 girls, aged from 16 to 19 years, who were high school students. 23 of the examined students had alcoholic parents. In the research the following tools were used : a socio-demographic Questionnaire, Survey to Examine the Internet Abuse created by Emilia Potembska, Internet Addiction Test created by Young, Questionnaire for Internet Addiction Studies (KBIU) created by Beata Pawłowska and Emilia Potembska, and The Questionnaire for the study of disturbed relationships in the family created by Beata Pawłowska.Results and conclusions: On the basis of the statistical analysis the following conclusions were drawn: 1. Daughters of alcoholics significantly more often treat the Internet and computer games as a way to forget about their reality and make themselves happy. 2. Mental and physical abuse of children who have alcoholic parents correlates with the children`s use of the web pornographic pages and playing violent computer games. 3. Children who lack acceptance, understanding and feel rejected by their families are of the opinion that only the Internet can give them a chance to express their true feelings, opinions , share their problems and gain acceptance and understanding.